1983
DOI: 10.1159/000123473
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Supra-Optic Nucleus to Brain and Pituitary Pools of Immunoreactive Vasopressin and Particular Opioid Peptides, and the Interrelationships between These, in the Rat

Abstract: Discrete, bilateral, radiofrequency destruction of the supra-optic nucleus resulted in a parallel fall in levels of immunoreactive (ir) dynorphin (DYN), ir-α-neoendorphin (α-NE) and ir-vasopressin (VP) in the hypothalamus, neuroin-termediate lobe (NIL) of the pituitary and septum of rats, whereas in the medulla/pons, midbrain and anterior lobe (AL), levels of these peptides were not significantly changed. The content of ir-β-endorphin (β-EP) was, in contrast, elevated in the hypothalamus and unchanged in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Watson et al (1982) have shown that immunoreactivity associated with dynorphin was colocalized with AVP in the hypothalamo-hypophyseal tract. In addition lesions of the supraoptic nucleus produce a parallel decrease in ir-AVP and ir-Dyn A in the NIL (Millan et al, 1983). The results of the present study d o not rule out the existence of a subpopulation of neurons in the magnocellular group in hypothalamus in which colocalization of dynorphinlike opioid peptides with AVP occurs.…”
Section: Discussioncontrasting
confidence: 88%
“…Watson et al (1982) have shown that immunoreactivity associated with dynorphin was colocalized with AVP in the hypothalamo-hypophyseal tract. In addition lesions of the supraoptic nucleus produce a parallel decrease in ir-AVP and ir-Dyn A in the NIL (Millan et al, 1983). The results of the present study d o not rule out the existence of a subpopulation of neurons in the magnocellular group in hypothalamus in which colocalization of dynorphinlike opioid peptides with AVP occurs.…”
Section: Discussioncontrasting
confidence: 88%
“…Thus the oxytocin and vasopressin neurones synthesize and process proenkephalin and prodynorphin respectively. However, on a molar basis the concentrations of opioid peptides in the rat neuro¬ hypophysis are at least a thousand-fold lower than those of oxytocin and vasopressin (Millan, Millan & Herz, 1983). There is thus considerable differentiation in the expression of the oxytocin/vasopressin and proenkephalin/pro-dynorphin genes.…”
Section: Opioids Monoamines and Gnrh Neuronesmentioning
confidence: 96%
“…We conclude that endogenous opioid peptides inhibit release of oxytocin in vivo by an effect on the final common pathway, i.e. the magnocellular neuron or on pituicytes in the neural lobe.A growing body of evidence supports a role for endoge nous opioid peptides in attenuating release of vasopressin and oxytocin from the hypothalamo-neurohypophysial sys tem [ 16,32] during osmotic and nonosmotic stimulation (22,27], Opioid peptides are localized both within magnocellu lar neurons that synthesize either vasopressin or oxytocin (13,35,36] and in the surrounding hypothalamus [15,17,18,25], In addition, opiate receptors are present in the neural lobe of the pituitary [28,34] and in the supraoptic and par aventricular nuclei of the hypothalamus [34]. Thus, both the cell bodies and nerve terminals of magnocellular neurons are sites where opioid peptides could attenuate secretion of neurohypophysial hormones.…”
mentioning
confidence: 99%